2021
DOI: 10.1111/tbed.14119
|View full text |Cite
|
Sign up to set email alerts
|

The new emerging ovine pestivirus can infect pigs and confers strong protection against classical swine fever virus

Abstract: Several emerging pestiviruses have been reported lately, some of which have proved to cause disease. Recently, a new ovine pestivirus (OVPV), isolated from aborted lambs, with high genetic identity to classical swine fever virus (CSFV), has proved to induce reproductive disorders in pregnant ewes. OVPV also generated strong serological and molecular cross‐reaction with CSFV. To assess the capacity of OVPV to infect swine, twelve piglets were infected either by intranasal or intramuscular route. Daily clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…It is worth highlighting the capacity of this virus to rapidly generate antibodies in swine after infection ( Wang et al., 2020b ), which in any case would favor reducing the circulating viral load and in turn reducing the possibility of OVPV cross-reactivity with test developed here. In addition, it’s unlikely that the cross-reaction of the LAMP test with OVPV would translate to a field setting, since the only study regarding experimental infection of pigs with OVPV showed that the viral RNA load detected in pigs after infection is much lower than that used for testing of the LAMP assay in the present study ( Bohórquez et al., 2021 ).…”
Section: Discussionmentioning
confidence: 65%
“…It is worth highlighting the capacity of this virus to rapidly generate antibodies in swine after infection ( Wang et al., 2020b ), which in any case would favor reducing the circulating viral load and in turn reducing the possibility of OVPV cross-reactivity with test developed here. In addition, it’s unlikely that the cross-reaction of the LAMP test with OVPV would translate to a field setting, since the only study regarding experimental infection of pigs with OVPV showed that the viral RNA load detected in pigs after infection is much lower than that used for testing of the LAMP assay in the present study ( Bohórquez et al., 2021 ).…”
Section: Discussionmentioning
confidence: 65%
“…The genetic and antigenic similarity of CSFV, TSV, and ovIT isolates complicates the demarcation of species in the genus Pestivirus. A close genetic and antigenic relationship between the ovIT isolates (Pestivirus O) and CSFV (Pestivirus C) has been recently reported and may cause problems in CSF molecular and serological diagnosis if the ovine pestiviruses are ever shown to be able to infect porcine hosts under natural conditions [50,51]. Genetic analysis based on p-distances was not suited to demarcate the species Pestivirus N and Pestivirus O, which are closely related to each other and to CSFV (Pestivirus C) as calculated distances lie in a range that do not show a clear affiliation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a clear discrimination to CSFV (Pestivirus C) might become challenging if viruses similar to TSV (Pestivirus N) and ovIT PeV (Pestivirus O) are found to cross the species barrier and efficiently infect and replicate in porcine hosts under natural conditions. In this context, it is important to emphasize that, despite close genetic and antigenic relatedness of CSFV (Pestivirus C), TSV (Pestivirus N), and ovIT PeV (Pestivirus O), clear differences exist in host specificity and clinical disease induced by both ruminant pestiviruses in comparison to CSFV (Pestivirus C) [39,51]. TSV (Pestivirus N) was discovered in 1995 and since that time, no natural infections have been reported in porcine hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the virulence of the double mutant virus was also evaluated in six 3-week-old pigs from Pestivirus -free sows (numbered 20 to 25), as in previous studies ( 43 , 44 ). The six pigs were inoculated intranasally with 2.5 × 10 4 TCID 50 s of vPdR-H 30 K-5U.…”
Section: Methodsmentioning
confidence: 99%